A forgotten grave monument in Apollonia (Albania) - Meta, Renald; Ritter, Jonathan (Archäologischer Anzeiger, 2022)
In 1988, during the extension of a modern water channel, an ancient monument was discovered in the plain west of Apollonia (Albania). While the excavators described it as an altar, this paper argues that the monument may be better interpreted as a tomb of the aedicula type as it is situated in the necropolis area close to the city wall. The monument is an important indicator of Apollonia’s funeral customs and raises questions regarding the funeral assemblies and areas of representation in Apollonia.